Applying the WaterGEMS Software to Conduct a Comparison of the Darcy-Weisbach and Hazen-Williams Equations for Calculating the Frictional Head Loss in a Selected Pipe Network (Journal of Engineering, 2023)
Darcy-Weisbach (D-W) is a typical resistance equation in pressured flow; however, some academics and engineers prefer Hazen-Williams (H-W) for assessing water distribution networks. The main difference is that the (D-W) friction factor changes with the Reynolds number, while the (H-W) coefficient is a constant value for a certain material. This study uses WaterGEMS CONNECT Edition update 1 to find an empirical relation between the (H-W) and (H-W) equations for two 400 mm and 500 mm pipe systems. The hydraulic model was done, and two scenarios were applied by changing the (H-W) coefficient to show the difference in results of head loss. The results showed a strong relationship between both equations with correlation coefficients of 0.999, 0.998, and 0.993 for 500 mm pipes and 0.998, 0.999, and 0.996 for 400 mm pipes for the applied scenarios. The results also showed that the head loss when using the (H-W) equation for old pipe is more than the (D-W) equation.